UJI SKRINING AKTIVITAS ANTIBAKTERI FRAKSI n-HEKSAN DAUN SEREH (Cymbopogon citrantus) TERHADAP BAKTERI PENYEBAB INFEKSI KULIT - Priatna, Nabilah Hana; Nuryanti, Siska; Rusli, Rusli (Makassar Pharmaceutical Science Journal (MPSJ), 2024)
Indonesia as a tropical country has a diversity of biological natural resources. This diversity is very beneficial, especially with the large number of plant species that can be used as medicine. One plant that is believed to be used as medicine is lemongrass which has lush and dense leaves. Lemongrass leaves (Cymbopogon citratus) is one of the medicinal plants and can be used as a kitchen spice. Lemongrass plants are very easy to find in Indonesia and contain alkaloids, saponins, tannins, polyphenols, flavonoids, and essential oils. Saponins and essential oils are the main group of chemicals that can exert activity against microbes. This study aims to conduct a screening test of antibacterial activity of the n-hexan fraction of lemongrass leaves (Cymbopogon citrantus) against bacteria that cause skin infections. This research method was conducted experimentally to test the antibacterial activity of lemongrass leaves by screening test. The results in this study, the n-hexan fraction of lemongrass leaves can inhibit the growth of test bacteria Staphylococcus aureus, Pseudomonas aureginosa, Staphylococcus epidermidis, and Propionibacterium acne. It can be concluded that lemongrass leaves (Cymbopogon citrantus) have antibacterial activity.